2020
DOI: 10.21109/kesmas.v15i2.2703
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effect of Aerosol Pesticide on Lung Dysfunction amongPaddy Farmers in Purworejo, Central Java, Indonesia

Abstract: The World Health Organization estimated that chronic obstructive pulmonary disease (COPD) will be the highest non-communicable disease worldwide by2030, and pesticide exposure is one of major risk factors. This study aimed to determine effect of pesticide exposure on lung dysfunction among paddyfarmers. A case-control study was performed on April - May 2016 in Purworejo. The case group comprised 66 farmers suffering from lung dysfunction during2015 based on medical records, while the control group comprised 59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…15 Studies in India and Indonesia had also shown lower FEV 1 /FVC ratio suggesting obstructive lung function and decrease FVC and FEV 1 suggesting restrictive lung function. 14,27…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Studies in India and Indonesia had also shown lower FEV 1 /FVC ratio suggesting obstructive lung function and decrease FVC and FEV 1 suggesting restrictive lung function. 14,27…”
Section: Discussionmentioning
confidence: 99%
“…15 Studies in India and Indonesia had also shown lower FEV 1 /FVC ratio suggesting obstructive lung function and decrease FVC and FEV 1 suggesting restrictive lung function. 14,27 Nonetheless, some studies failed to identify any association between pesticide exposure and lung function. This may happened because perceptions regarding the harmful health effects, knowledge about pesticide spraying practices, and adherence to use personal protective equipment differ among countries.…”
Section: Discussionmentioning
confidence: 99%